Ethnographic Worldviews Transformations and Social Justice - Rinehart, Robert E.; Barbour, Karen N.; Pope, Clive C.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This book discusses ethnography from the three points of view of Emerging Methodologies, Practice and Advocacy, and Social Justice and Transformation, with an over arching emphasis on researchers' and participants' worldviews. While these three thematic threads cut across each other, the actual chapters will be located so that the reader understands many of the current issues and concerns-with specific exemplars from around the globe-for ethnographers. 'Ethnographic Worldviews: Transformations and Social Justice' will have its "finger on the pulse" of contemporary ethnography. Chapters demonstrate up-to-the-moment awareness of ethnographic methods, concerns, and subject matters within contemporary ethnographic writing. Authors are deeply engaged in both their subject matter and their method. Unlike other ethnographic books which often suggest "giving voice to others", this book will actually give voice to a wide variety of perspectives, from the points of view of researchers.
Chapter 1. Proem: Engaging Contemporary Ethnography Across the Disciplines; Robert E. Rinehart, Karen Barbour and Clive Pope -- Part I. Social Justice and Transformation: Theoretical Ethnographic Visions -- Chapter 2. Social Justice, Transformation and Indigenous Methodologies -- Linda Tuhiwai Smith -- Chapter 3. Voices of Women in Post-Apartheid South Africa: Visual Narrative, Social Justice and Empowerment; Annette Blum -- Chapter 4. Advanced Marginalization and Re-Criminalization of Undocumented Immigrants in the Post-Neoliberal State; Kennosuke Tanaka -- Chapter 5 -- Rethinking English in Maori Medium Education; Richard Hill -- Chapter 6. Negotiating Safe and Unsafe Space: Participation, Discomfort and Response-Ability in Higher Education Institute Transformation in South Africa; Helen MacDonald -- Part II. Practice and Advocacy: Doing Ethnography on the Ground -- Chapter 7. Living and Learning Together: Principled Practice for Engagement and Social Transformation in the East Kimberley Region of Western Australia; Neil Drew -- Chapter 8. The Journey to a Good Life: Exploring Personal and Organizational Transformation through Digital Storytelling; Elaine Bliss and Janelle Fisher -- Chapter 9. Toi tu te Whenua, Toi tu te Tangata: A Holistic Maori Approach to Flood Management; Elizabeth-Mary Proctor -- Chapter 10. One woman, one too many; Lisa M. Hayes -- Chapter 11. Co-creating visual theories of change with Treaty and decolonization activists; Ingrid L. M. Huygens -- Part III. Emerging Methods: Traditional, Experimental, Transgressive Forms -- Chapter 12. Sustaining Fish-Human Communities? A More-than-Human Question; Elspeth Probyn -- Chapter 13. An "insider's view" in Media Studies: Case Analysis of Performance Ethnography in Mobile Media Studies; Yonnie Kyoung-haw Kim -- Chapter 14. Erica$1 (Bs Story: A Poetic Representation of Loss and Struggle; Vivienne Elizabeth, Nicola Gavey and Julia Tolmie -- Part IV. Afterword -- Chapter 15. A Critical Performance Ethnography that Matters; Norman K. Denzin.s
Keywords: Social sciences; Regional planning; Anthropology; Applied psychology; Social Sciences; Anthropology; Regional and Cultural Studies; Cross Cultural Psychology